New Approach to Liberia Population and Housing Census : From Traditional Based to Combined Approach - Williams, G Alex M; Mazouch, Petr, 1981-; Novák, Jiří; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2020)
This thesis aims to define the future of population statistics in Liberia by providing a roadmap on how Liberia could leverage on the experiences of other nations to transition from a traditional-based census to a combined approach. It is the view of the author that the Combined Census approach would not only improve the quality of population statistics in Liberia but is also a cost-saving method for Liberia, especially as a poor and underdeveloped nation.
Vedoucí práce: Petr Mazouch
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: official statistics [obor dipl. práce]; diplomové práce; master's theses